PENGEMBANGAN APPLET GEOGEBRA PADA MATERI DISTRIBUSI PELUANG KHUSUS - Rina Susilowati; M. Julkarnain (Jurnal Informatika Teknologi dan Sains, 2022)
The use of technology in education, especially in mathematics is very important. It is critical to create technology-based learning media such as the Geogebra applet so that students can learn independently in constructing understanding concepts to solve mathematical problems through modeling, simulation, and visualization. This study aims to develop a geogebra applet on a valid and practical special probability distribution material.. The type of research used is development research with reference to the development design of the Three-D (3D) model. Data collection techniques include questionnaires, observations, and interviews. Data from observations and interviews were analyzed qualitatively. The data from the validation and practicality tests were analyzed using descriptive quantitative analysis. Based on the results of data analysis, it was found that the average percentage of validation results was 85.47%, so it can be said that this geogebra applet was categorized as very valid.. The results of the student response questionnaire on aspects of pleasure, usefulness, convenience, and interest in the display reached an average percentage of 85.63% and was categorized as very practical, so the geogebra applet that was developed could be used in learning.